Targeting the RdRp of Emerging RNA Viruses: The Structure-Based Drug Design Challenge - Francesca Picarazzi; Ilaria Vicenti; Francesco Saladini; Maurizio Zazzi; Mattia Mori (Molecules, 2020)
The RNA-dependent RNA polymerase (RdRp) is an essential enzyme for the viral replication process, catalyzing the viral RNA synthesis using a metal ion-dependent mechanism. In recent years, RdRp has emerged as an optimal target for the development of antiviral drugs, as demonstrated by recent approvals of sofosbuvir and remdesivir against Hepatitis C virus (HCV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), respectively. In this work, we overview the main sequence and structural features of the RdRp of emerging RNA viruses such as Coronaviruses, Flaviviruses, and HCV, as well as inhibition strategies implemented so far. While analyzing the structural information available on the RdRp of emerging RNA viruses, we provide examples of success stories such as for HCV and SARS-CoV-2. In contrast, Flaviviruses’ story has raised attention about how the lack of structural details on catalytically-competent or ligand-bound RdRp strongly hampers the application of structure-based drug design, either in repurposing and conventional approaches.